Grey Literature Review of the Undergraduate Theses of the Bicol University Computer Science Program - Rodriguez, Ryan A.; Balilo Jr., Benedicto B.; Vibar, Jayvee Christopher N. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The purpose of this research is to examine the undergraduate thesis methodology, programming languages, and databases utilized to create thesis projects. The study's findings will open a wide range of researchable topics and will usher in new trends in computer science. There will be new insights in developing and proposing thesis proposals which will introduce various applications of a prospective research study. Method – The manuscript from 2005 to 2019 served as initial information with the name of students, advisers, and panel members.  The titles are converted into lowercase characters for easy categorization utilizing the features MS Excel transposition method and PivotTable.   Special symbols like dash, colon, parentheses, slash, and apostrophe are removed to provide a list of common words.  Standard frequency count and categorization of special project titles were used to count per year, filter, and categorize the titles according to keywords.   Results – The study showed that students are familiar with different methodologies, programming languages, databases, types of development, and application tools in writing special projects.  Most projects are inclined toward a desktop application that uses Visual Basic as the programming language. Conclusion – In software development, they used application tools to support the development process of the applications, and they used open-source tools. The type of study or research dictates the right decision in choosing the right methodologies to meet the study’s objectives. They used tools to improve their design, convenient interaction with programming languages, and practical wise for faster development. Recommendations – The results will be an opportunity to expose and explore computer science researchable areas, especially theories and concepts of computing.  The study results shall serve as Manuscripts that are valuable assets of the institutions and should be preserved.   Research Implications – Capstone initiatives significantly contribute to the government, academia, business, cooperatives, religious institutions, and private groups. Approximately 60% of capstone projects are directly related to or have resulted in information systems for the organization. This advancement significantly affected the ITE program's directions, and the study established research options, including the capstone project's proposed research fields. Furthermore, supply excellent inputs to academic programs that will open new trends in researchable domains. Once students begin to submit capstone projects, this may have an impact on the research fields of the IT degree program.